Tout ton flottant bas autorise-t-il la propogation du ton haut précedent en Dagara-Wule.pdf - Penou-Achille Somé (LibraryPress@UF, 2001)
This study addresses the syntactic implications of low floating tones in Wule, one of the three varieties of Dagara, a language of the Voltai'c Group spoken in the northern part of Ghana and the southern part of Burkina Faso, The data show that if "peripheral" low floating tones allow a high preceding tone to spread, it is the other way around for "internal" low floating tones, In fact, the latter type of tones, like opaque consonants, always prevents a high preceding tone from spreading, This result leads to a question concerning the relationship between internal low floating tones and opaque consonants, After debating two different assumptions, it has been retained that, despite the similar syntactic implications, internal low floating tones and opaque consonants are two different linguistic entities which do not have, as such, any historical link.